'Real Play Families': a New Zealand case study. Issue 1 (2nd January 2018) - Walters, Simon R.; Duncan, Scott; McPhee, Julia; Atkins, Denise; Millar, Sarah-Kate
ABSTRACT: This case study examined the experiences of three New Zealand families selected to participate in a four-week 'Real Play Families' project. The overall aim of the project was to explore the issues faced when embedding traditional, unstructured, and largely unsupervised play practices in the modern family environment. The project commenced with an initial workshop day, including a two-hour information seminar for parents, real play activities for the children, and a combined debriefing session. Data from parent and child focus group interviews and social media postings were reviewed to generate a comprehensive, triangulated picture of the experiences of each family. The analysis focused on how the families derived meaning and value out of real play, drawing upon their initial perspectives, experiences, challenges, and post-project reflections. Our findings suggest that providing families with appropriate advice and social support around real play can prompt positive and rewarding outcomes for children and parents.